Sleep disturbance in children with rett syndrome: A qualitative investigation of the parental experience - McDougall, A; Kerr, A; Espie, C (2005)
Background Sleep problems in children with intellectual disability can be precipitated and maintained by intrinsic and external factors. The present study comprised a qualitative investigation of the experiences of parents of children with Rett syndrome, a neurodevelopmental disorder where sleep disturbance is common. Method Audio-taped interviews were conducted with nine families. Transcripts were analysed by theoretical coding to develop categories and themes, facilitated by the computer package QSR NUD*IST.Results Themes and sub-themes were identified in the areas of (1) parents' beliefs about sleep problems, (2) coping with sleep problems, and (3) emotions, and an interactional model of the three systems was suggested. Conclusions A proposed interactional model of parental beliefs, coping and emotions in relation to sleep disturbance in children with Rett syndrome is consistent with existing theoretical models. Further research is required to test out the applicability of this conceptual framework to parents of children with other aetiologies of intellectual disability. © 2005 BILD Publications.